2022
DOI: 10.3390/su142013335
|View full text |Cite
|
Sign up to set email alerts
|

Religious Tourists’ Satisfaction with Services and Their Impacts on Spirituality in the Post-COVID-19 Era

Abstract: Islamic pilgrimage has social, political, and economic benefits, but there are major challenges in the management of large numbers of groups at one time. This spiritually healing journey is likely to be influenced by the overall experience and the quality of logistical services provided while performing the rituals. In the postpandemic period, challenges were more apparent in preventing the spread of infection while maintaining acceptable levels of spiritual atmosphere. Pilgrims’ characteristics might mediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition, the company recognizes the importance of personalized service in the Umrah travel industry. Understanding that each pilgrim's journey is unique, the company tailors its services to accommodate individual needs, fostering a sense of care and consideration that goes beyond the transactional aspects of the journey (Hassan et al, 2022). To mitigate common challenges faced by pilgrims, such as visa issues, flight delays, or accommodation changes, the company uses a proactive approach (Nurohman, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the company recognizes the importance of personalized service in the Umrah travel industry. Understanding that each pilgrim's journey is unique, the company tailors its services to accommodate individual needs, fostering a sense of care and consideration that goes beyond the transactional aspects of the journey (Hassan et al, 2022). To mitigate common challenges faced by pilgrims, such as visa issues, flight delays, or accommodation changes, the company uses a proactive approach (Nurohman, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Liu [15] revealed that social distancing affects purchase intentions in the restaurant and hotel sectors. Hassan et al [16] examined the satisfaction of religious tourists in the post-COVID-19 situation.…”
Section: Introductionmentioning
confidence: 99%